Transregionalism: Underlying Concept of EAEU-ASEAN Cooperation and Greater Eurasian Partnership - Anna A. Garmash (Сравнительная политика)
Nowadays the EAEU seeks to integrate itself into the global economy as one of its regional economic centers. Developing ties with other regional integration groups corresponds the EAEU’s interests and facilitates the polycentric structure of the emerging world order. In this respect, in 2016 on the sidelines of the third Russia-ASEAN Summit Russian President Vladimir Putin proposed to develop stronger relations between the EAEU and ASEAN as well as to form a greater Eurasian partnership encompassing the EAEU, the SCO and ASEAN. While geographically vast, these projects lack conceptual underpinning. It is deemed that transregionalism – an international phenomenon which is insuffi ciently explored by both Western and Russian scholars, can provide a crucial theoretical foundation for these initiatives. The author compares the mechanisms which ASEAN employs to promote transregional cooperation with the EU, MERCOSUR and the GCC as well as within the frameworks of such dialogue platforms as ASEM and FEALAC. The author suggests that EAEU-ASEAN relations should be analyzed from the viewpoint of a classic transregionalism, while a greater Eurasian partnership seen as an example of a broader one. The results of the analysis are instrumental in laying out practical recommendations for the EAEU in carrying out its transregional agenda.